Transport Properties, Mechanical Behavior, Thermal and Chemical Resistance of Asymmetric Flat Sheet Membrane Prepared from PSf/PVDF Blended Membrane on Gauze Supporting Layer - Nita Kusumawati; Pirim Setiarso; Maria Monica Sianita; Supari Muslim (Universitas Gadjah Mada, 2018)
Asymmetric polysulfone (PSf) membrane is prepared using phase inversion method and blending with polyvinylidene fluoride (PVDF) on the gauze solid support. Casting solution composition optimization has been done to get PSf/PVDF membrane with best characteristics and permeability. The result shows that blending on PSf with PVDF polymer using phase inversion method has been very helpful in creating an asymmetric porous membrane. Increased level of PVDF in casting solution has increased the formation of asymmetry structure and corresponding flux membrane. The result from thermal test using Differential Scanning Calorimetry (DSC)-Thermal Gravimetric Analysis (TGA) shows the resistance of the membrane to temperature 460 °C. Membrane resistance against acid looks from undetectable changes on infrared spectra after immersion process in H2SO4 6–98 v/v%. While membrane color changes from white to brownish and black is detected after the immersion process in sodium hydroxide (NaOH) 0.15–80 w/v%.